Smart Management of Conservative, Organic and Integrated Agriculture - Peruzzi, Andrea; Frasconi, Christian; Antichi, Daniele (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Sustainable agriculture aims to achieve the goal of food security, also maximizing the socio-economic benefits, and minimizing environmental drawbacks. Farming systems mostly relying on ecological processes and the reduced application of external inputs (fertilizers and pesticides), such as organic farming and integrated farming, can even contribute to the mitigation of global warming and of the desertification of soils. Conservation agriculture (CA) is also widely recognized as a farming system able to preserve soils from erosion and nutrient loss, increase soil organic matter and carbon sink capacity, and improve biological and physical fertility. Nevertheless, CA systems generally rely on the large use of agrochemicals (above all, herbicides and fertilizers) in order to sustain crop production, with negative consequences in terms of energy efficiency and environmental impact. This also does not enable an easy transfer of CA techniques into organic and integrated farming systems, a combination that might enhance the environmental benefits of these farming systems. In this regard, this Special Issue deals with the "Smart Management of Conservative, Organic, and Integrated Agriculture". We invited experts and researchers to contribute with original researches, reviews, and opinion pieces covering all topics related to organic, integrated, and conservative farming systems. The published articles concern with the most important aspects of these innovative systems, such as performances of farm machinery and agro-ecological strategies aiming at sustaining crop production whilst reducing the need for agrochemicals.